2001
DOI: 10.1093/ps/80.3.289
|View full text |Cite
|
Sign up to set email alerts
|

Sodium and Chloride Requirements of Growing Broiler Chickens (Twenty-one to Forty-two Days of Age) Fed Corn-Soybean Diets

Abstract: Two trials were conducted to determine Na+ and Cl- nutritional requirements and dietary electrolyte balance (DEB) and its effects on acid-base balance, litter moisture, and incidence of tibial dyschondroplasia (TD) in broiler chickens during the growing period. Cobb broilers were distributed in a completely randomized design (30 pens) with six treatments, five replicates, and 50 birds per experimental unit at 21 d of age. Treatments used in both trials were a basal diet with 0.10% Na+ (Trial 1) or Cl- (Trial 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
0
17

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 17 publications
6
29
0
17
Order By: Relevance
“…When 20% of glycerin was supplemented a 0,6% of sodium also was incorporated to the diet. Murakami et al (2001) and Borges et al (1998) observed a linearity between sodium increment and litter humidity. Nevertheless, independently of sodium effect, Gianfelici (2008) supplementing pure glycerol (p.a) in another experiment, also observed the same phenomenon, i.e, the increase in urine production above 10% of glycerol in the diet .…”
Section: Determination Of Apparent Metabolizable Energy Of Crude Glycmentioning
confidence: 89%
“…When 20% of glycerin was supplemented a 0,6% of sodium also was incorporated to the diet. Murakami et al (2001) and Borges et al (1998) observed a linearity between sodium increment and litter humidity. Nevertheless, independently of sodium effect, Gianfelici (2008) supplementing pure glycerol (p.a) in another experiment, also observed the same phenomenon, i.e, the increase in urine production above 10% of glycerol in the diet .…”
Section: Determination Of Apparent Metabolizable Energy Of Crude Glycmentioning
confidence: 89%
“…Estudando a exigência de cloro e sódio para poedeiras comerciais, Murakami et al, (2001b) também não verificaram influência significativa do nível de cloro sobre a umidade das excretas das aves. Segundo Rondon et al (2001) e Murakami et al (2001a) quando o nível de cloro da ração está em proporção adequada ao nível de sódio, não há aumentos significativos na excreção renal, consequentemente, não ocorre aumento na umidade das excretas. Por sua vez, Mushtaq et al (2007) relataram que a umidade da cama tende a diminuir com o aumento dos níveis de cloro das rações.…”
Section: Resultsunclassified
“…O cloro (Cl) é encontrado nas células, nos fluídos extracelulares do organismo, principalmente na forma de cloreto de sódio e cloreto de potássio, e no suco gástrico, como ácido clorídrico (MURAKAMI et al, 2006). O cloro, juntamente com o sódio e o potássio, auxiliam na manutenção do equilíbrio ácido-básico, e podem influenciar o apetite, o desenvolvimento ósseo, o crescimento, a resposta ao estresse térmico e o metabolismo de certos nutrientes, como aminoácidos, minerais e vitaminas afetando o desempenho das aves na fase inicial e, posteriormente, na fase de produção.…”
Section: Introductionunclassified
“…Segundo Pinheiro et al (2011), tem sido relatado que rações com altos teores de Cl-diminuem o pH sanguíneo em frangos, prejudicando o seu crescimento, enquanto, a deficiência afeta negativamente o crescimento, causando distúrbios nervosos. Contudo, apesar da importância do cloro na alimentação das aves, as exigências desse mineral têm sido pouco estudadas, talvez pelo fato das necessidades de sódio e cloro serem supridas pelo cloreto de sódio (NaCl -sal comum), um ingrediente de baixo custo normalmente adicionado às formulações (MURAKAMI et al, 2006).…”
Section: Introductionunclassified